2012
DOI: 10.1155/2012/761450
|View full text |Cite
|
Sign up to set email alerts
|

Attenuating Effect ofGinkgo bilobaLeaves Extract on Liver Fibrosis Induced by Thioacetamide in Mice

Abstract: The purpose of this study is to investigate the effect of Ginkgo biloba leaves extract on experimental liver fibrosis induced by thioacetamide (TAA) in male albino mice. The experimental mice were divided into four groups. The mice of the first group were served as control. The experimental animals of the second group were given 150 mg/kg body weight of TAA by intraperitoneal injection, twice weekly, for 9 weeks. The mice of the third group were exposed to TAA and supplemented with G. biloba leaves extract. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 59 publications
2
17
0
Order By: Relevance
“…In many cases TAA has been used to create a model of hepato-toxicity. These agents include reynosin (Lim et al, 2013), Ginkgo biloba leaves extract (Al-Attar, 2012) and ethanolic and aqueous extracts of Phyllanthus acidus (L.) Skeels ( P. Acidus ; Jain and Singhai, 2011), etc. An imidazolium salt, 1,3-diisopropylimidazolium tetrafluoroborate (DPIM) has also been shown to reduce TAA-induced mouse liver injury (Ding and Zhuo, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…In many cases TAA has been used to create a model of hepato-toxicity. These agents include reynosin (Lim et al, 2013), Ginkgo biloba leaves extract (Al-Attar, 2012) and ethanolic and aqueous extracts of Phyllanthus acidus (L.) Skeels ( P. Acidus ; Jain and Singhai, 2011), etc. An imidazolium salt, 1,3-diisopropylimidazolium tetrafluoroborate (DPIM) has also been shown to reduce TAA-induced mouse liver injury (Ding and Zhuo, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al 2006 [39] demonstrated that the histopathological score of fibrosis and liver function were significantly improved in rats treated with ccl4 plus G. biloba extract, compared with those treated with ccl4 only. Zhang et al 2008 [40] reported that G. biloba extract EGb 761 alleviates hepatic fibrosis and sinusoidal microcirculation disturbance in patients with chronic hepatitis B. Al-Attar, 2012 [21] showed that G. biloba leaves extract has a potential activity against thioacetamide-induced liver fibrosis and suggested that the chemical constituents of G. biloba are effective in modulation of oxidative stress induced by thioacetamide.…”
Section: Discussionmentioning
confidence: 99%
“…Sener et al 2005 [20] assessed the antioxidant and antifibrotic effects of long-term G.biloba extract administration on liver fibrosis induced by bile duct ligation (BDL) and scission in Wistar male albino rats. Recently, Al-Attar, 2012 [21] reported that G. biloba leaves extract inhibits liver fibrosis induced by thioacetamide in mice. The present study was designed to evaluate the protective effect of G. biloba leaves extract on hepatotoxicity of carbendazim in albino rats.…”
Section: Introductionmentioning
confidence: 99%
“…To measure bilirubin, azo DVD reagents (sulfanilic acid sodium nitrite) were used; they react with bilirubin, producing azo, which is red in alkaline PH. After production, direct bilirubin has a pink color, but after addition of accelerating solution, total bilirubin turns green in alkaline PH [17].…”
Section: Biochemical Studymentioning
confidence: 99%